3h-h+2h-2h-h=3

Simple and best practice solution for 3h-h+2h-2h-h=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3h-h+2h-2h-h=3 equation:



3h-h+2h-2h-h=3
We move all terms to the left:
3h-h+2h-2h-h-(3)=0
We add all the numbers together, and all the variables
h-3=0
We move all terms containing h to the left, all other terms to the right
h=3

See similar equations:

| 5x-22=60 | | 3x+2=5x=16 | | -16+18t=16+20t | | 5v+6=-9 | | 28=2+6(z-8) | | x/11+17=0 | | 9s-3s-5s=14 | | -19+11j=12j | | 10x+x+x=18 | | -13b=8 | | -l6=(-2)l+9 | | 3x^2+5x+20=16+x+x^2 | | 6b-2b-5b=1+14-7 | | 18d-12d+3D=10 | | x/8+4=-12 | | -7y-13=5y+11 | | –3=4-y/3 | | y-16+2y+118=180 | | 16x^2-4x=6 | | 6j-5j=10 | | 9c-8c=15 | | y-17+2y+118=180 | | 7/5x-9.42-2/5x-1.58=0 | | -x/12+25=29 | | -2x^2-4x-1=2x+4 | | -9+n=11/ | | -5(3c-9)=35-8c | | 23=1.5x+20 | | 3x+50+5x+12=180 | | -17+2(6x-1)+5=0 | | 3*2x-5=4x+7 | | 3(x+4)-4=2(2x+5)-x |

Equations solver categories